The importance of dead material within a tumour on the dynamics in response to radiotherapy - Lewin, TD; Byrne, HM; Maini, PK; Caudell, JJ; Moros, EG; Enderling, H (IOP Publishing, 2019)
In vivo tumours are highly heterogeneous, often comprising regions of hypoxia and necrosis. Radiotherapy significantly alters the intratumoural composition. Moreover, radiation-induced cell death may occur via a number of different mechanisms that act over different timescales. Dead material may therefore occupy a significant portion of the tumour volume for some time after irradiation and may affect the subsequent tumour dynamics.